1999
DOI: 10.1016/s0014-5793(99)01327-7
|View full text |Cite
|
Sign up to set email alerts
|

The cadherin‐like protein is essential to specificity determination and cytotoxic action of the Bacillus thuringiensis insecticidal CryIAa toxin

Abstract: The Bacillus thuringiensis CryIAa toxin binds a cadherin-like protein (BtR175) on the brush-border membranes of the Bombyx mori midgut columnar cells, which are the targets. By introducing the BtR175 gene with a baculovirus, Spodoptera frugiperda Sf9 cells expressed BtR175 protein on the cell membrane and became susceptible to the CryIAa toxin. The toxin bound the cadherin repeat adjacent to the membrane and made a pore that passed inorganic ions, causing the cell to swell and burst. This was not observed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 27 publications
4
110
1
Order By: Relevance
“…1B and Movie 1). Cell swelling and lysis occurred within a short time frame (30-40 min after toxin exposure), a phenomenon also observed in other insect cells (9,40) as well as in mammalian cells transfected with the cDNA of BT-R receptors (11). The morphological changes observed in Cry1Ab toxin-treated cells (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…1B and Movie 1). Cell swelling and lysis occurred within a short time frame (30-40 min after toxin exposure), a phenomenon also observed in other insect cells (9,40) as well as in mammalian cells transfected with the cDNA of BT-R receptors (11). The morphological changes observed in Cry1Ab toxin-treated cells (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…Various types of insect cell lines have also been studied for their toxicity response to different Cry proteins (25,26), and it was found that Sf-9 cells showed very less toxicity to Cry1Ab and showed maximum toxicity with Cry1C (27). The effectiveness of using live insect cells expressing putative receptor proteins and demonstrating the ability of the protein to function as a receptor to Bt toxin has been shown by Nagamatsu (10). They have been able to demonstrate swelling and lysis of Sf-9 cells expressing cadherin protein of B. mori after overlay with Cry1Ab toxin.…”
Section: Discussionmentioning
confidence: 99%
“…Two membrane proteins, cadherin and aminopeptidase-N (APN), have been implicated as possible receptors to insecticidal proteins. The putative receptor molecules have been cloned, heterologously expressed, and have been shown to bind Cry1A proteins by ligand blot analysis (4)(5)(6)(7)(8)(9)(10)(11). Although functional proof for cadherin as a Cry1A protein receptor has been demonstrated by cytolysis of insect cells expressing lepidopteran cadherin genes on exposure to Cry1Ab/Cry1Aa (10,12,13), a similar characterization of APN-Cry1A interaction has not been investigated yet.…”
mentioning
confidence: 99%
“…Independently, a 210-kDa cadherin-like protein from M. sexta was shown to interact with Cry1Ab toxin (6) and later its presence and toxin interaction was also demonstrated from another insect, Bombyx mori (7). Relative abundance of APN in the posterior midgut (8) and lower binding constants of Cry toxin toward cadherin as compared with APN (9) raised apprehension about the role of APN as a receptor for Bt toxin in the insect midgut.…”
Section: Insecticidal Crystal Proteins Of Bacillus Thuringiensismentioning
confidence: 99%